Farewell Luncheon at Cedar Lanes Bowling Alley for Tomar Mason II - Watkins, Howard::::::::: (1986)
Don Penner speaking about Tomar Mason; Galen Larson, Tomar's mother-Tomar Mason; Tomar Mason II, her father-William Mason, Justice Pauline Davis Hanson